Robert Egevang & Ulla Haastrup (red.): Danske kalkmalerier. Romansk tid 1080-1175. (Christian Ejlers' Forlag, 1986). Robert Egevang & Ulla Haastrup (red.): Danske kalkmalerier. Gotik 1375-1475. (Christian Ejlers' Forlag, 1985). - Munk-Jørgensen, Wivan (Historie/Jyske Samlinger, 1989)
Robert Egevang & Ulla Haastrup (red.): Danske kalkmalerier. Romansk tid 1080-1175. (Christian Ejlers' Forlag, 1986). 206 s. illustr. Robert Egevang & Ulla Haastrup (red.): Danske kalkmalerier. Gotik 1375-1475. (Christian Ejlers' Forlag, 1985). 208 s. illustr.